2020
DOI: 10.1007/s12144-020-00758-5
|View full text |Cite
|
Sign up to set email alerts
|

A contextually adapted model of school engagement in Kazakhstan

Abstract: This study introduces a culturally adapted 17-item scale of school engagement. It offers an important contribution to the international literature by seeking to measure the school engagement of young people in a society undergoing transition from a collectivist to individualist mind-set alongside an education system focused on improving performance in international benchmarks such as those from the Organisation for Economic Cooperation and Development (OECD Programme for International Student Assessment, PISA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
3
0
1
Order By: Relevance
“…Another specific feature of gifted students’ adjustment experiences at the university level is a habit of comparing their performance with other students, stemmed from their school background, sense of perfectionism, and high personal expectations developed in highly demanding competitive atmosphere in their selective schools (Speirs Neumeister, 2004; Winter et al, 2020). Those students who entered the highly selective programs at university were most likely to be the top performers from their schools, and it was particularly challenging for them to realize that someone might have superior ability and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Another specific feature of gifted students’ adjustment experiences at the university level is a habit of comparing their performance with other students, stemmed from their school background, sense of perfectionism, and high personal expectations developed in highly demanding competitive atmosphere in their selective schools (Speirs Neumeister, 2004; Winter et al, 2020). Those students who entered the highly selective programs at university were most likely to be the top performers from their schools, and it was particularly challenging for them to realize that someone might have superior ability and performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although many cross‐sectional and longitudinal studies are found to have examined the concepts of self‐regulation and role model separately (Abdollahi et al, 2018; Han, 2022; Khodarahmi & Zarrinabadi, 2016; Pell et al, 2022; Truskauskaitė‐Kunevičienė et al, 2020; Winter et al, 2020), less information is available about the relationship between these two concepts. However, the perception of role modeling is an important predictor regarding the development of self‐regulation skills (Karaca & Bektas, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kazakhstan is in fact a diverse country with more than 120 ethnic groups that have different social values and norms ( The Agency on Statistics of the Republic of Kazakhstan, 2011 ). Second, as a former Soviet republic, Kazakhstan maintains a strong national collectivist tradition ( Winter et al, 2020 ). This is relevant as collectivist cultures tend to demonstrate stronger and more consistent magnitudes and patterns of SDB ( Bernardi, 2006 ; Kim and Kim, 2016 ).…”
Section: Introductionmentioning
confidence: 99%